Aplikasi Pembelajaran Jaringan Komputer Berbasis Android - Novita, Vianny; Handojo, Andreas; Noertjahyana, Agustinus (Jurnal Infra, 2015)
Nowadays, in the era that technology grows rapidly, computer network is not something new to be learnt. Almost every company uses a computer network to facilitate the transfer of data and information. Internet, the huge computer network, is popular and is not a novel matter to most people. Many devices can interact with each other using internet. Computer networks themselves have components that mutually support each other, including Server and Router. An understanding of computer networks can be used to perform the analysis when there is a problem in the network.Therefore, this thesis was made with the aim of helping people to understand how a computer network works. This application is supported by the distributuin of structured subjects, making them easier to undertand. Each subject also includes images corresponding to the subject being discussed.The experimental results show that the application can work well on different Android devices. Everytime the application is started, the user needs to provide connection for the system to download data, text, and images.